Foreign students at the University of Salamanca during the second half of Franco's regime (1955-1971) - Sara GONZÁLEZ GÓMEZ (Ediciones Universidad de Salamanca, 2012)
Students are a fundamental and essential part of an educational institution. A survey of these students constitutes a key aspect of the research devoted to the History of Universities. For this reason, the reflection on the group formed by foreign students at the university can give us valuable information on institutional life during a particular chronological period. The University of Salamanca has built up, with the passage of time, a reputation that has become a benchmark for institutions, teachers and students. Even though during Franco's Regime it did not go through one of its best moments, a quick glace at the presence of foreign university students in Salamanca during the period 1955 to 1971, reveals some suggestive evidence for research. The number, the geographical origin or their choice of subject areas are some of the issues discussed in this paper. We also analyze some phenomena such as associationism or certain academic initiatives that related to foreign students. All with the aim of providing a clear picture of the foreign group at the University of Salamanca during the second half of Franco's Regime.